Ahead of the Curve: Leveraging Antecedents of Corporate Entrepreneurship to Pull Off Competitive Advantage - Mahmood, Asif; Arslan, Ahmad (Frontiers in Psychology, 2020)
Entrepreneurship is a highly dynamic and important endeavor that spills over to economic, technological, and social canvas of a society in this rapidly changing globalized economy. The purpose of present quantitative study is to investigate the association between information and communication technologies, innovation, absorptive capacity, CEO’s temporal leadership and competitive advantage by considering corporate entrepreneurship as mediator. These factors have been incorporated because they play very important role to compete in a competitive environment for entrepreneurial success and economic growth. Data have been collected through questionnaire, and Structural Equation Modeling has been employed to analyze the measurement and structural relationships as well as the mediation effects of corporate entrepreneurship. We used sample of 460 organizations to examine how antecedents of corporate entrepreneurship respond towards competitive advantage. All the relationships with corporate entrepreneurship found to be significant, establishing corporate entrepreneurship as mediator to predict competitive advantage. Practically, the study would be invaluable for organizations, entrepreneurs and managers to capture a lot of opportunities in effectively managing the scarce resources.